Detecção e caracterização molecular de Cryptosporidium spp. em canários mantidos em cativeiro (Serinus canaria) por diferentes métodos de diagnóstico - Camargo, Vinícius da Silva [UNESP]; Santana, Bruna Nicoleti [UNESP]; Ferrari, Elis Domingos [UNESP]; Nakamura, Alex Akira; Nagata, Walter Bertequini [UNESP]; Nardi, Ana Rita Moraes; Meireles, Marcelo Vasconcelos [UNESP] (FapUNIFESP (SciELO), 2018)
This study used several diagnostic methods to examine the occurrence of and molecularly characterize Cryptosporidium spp. in captive canaries (Serinus canaria) in southern and southeastern Brazil. A total of 498 fecal samples were purified by centrifugal-flotation using Sheather’s solution. Cryptosporidium spp. diagnosis was performed using three diagnostic methods: malachite green negative staining, nested PCR targeting the 18S rRNA gene, followed by sequencing the amplified fragments, and duplex real-time PCR targeting the 18S rRNA specific to detect Cryptosporidium galli and Cryptosporidium avian genotype III. The overall positivity for Cryptosporidium spp. (total samples positive in at least one protocol) from the microscopic analysis, nested PCR and duplex real-time PCR protocol results was 13.3% (66/498). The positivity rates were 2.0% (10/498) and 4.6% (23/498) for Cryptosporidium spp. by microscopy and nested PCR, respectively. Sequencing of 20 samples amplified by nested PCR identified C. galli (3.0%; 15/498), Cryptosporidium avian genotype I (0.8%; 4/498) and Cryptosporidium avium (0.2%; 1/498). Duplex real-time PCR revealed a positivity of 7.8% (39/498) for C. galli and 2.4% (12/498) for avian genotype III. Malachite green negative staining differed significantly from nested PCR in detecting Cryptosporidium spp. Duplex real-time PCR was more sensitive than nested PCR/sequencing for detecting gastric Cryptosporidium in canaries.
Detection and molecular characterization of Cryptosporidium spp. in captive canaries (Serinus canaria) using different diagnostic methods
Keywords: Birds; Cryptosporidiosis; Diagnosis; Epidemiology